Bioinspired piezoelectric patch design for sonodynamic therapy: a preclinical mechanistic evaluation of rotator cuff repair and functional regeneration - Shi, Rui; Liu, Fei; Qin, Qihuang; Li, Pinxue; Huo, Ziqi; Zhou, You; Jiang, Chunyan (Frontiers in Bioengineering and Biotechnology, 2025)
IndroductionThe rotator cuff tendon-bone interface exhibits a gradient histological composition, including graded mineral content and interwoven collagen fibers. Following rotator cuff injury repair, the lack of a compositional, structural, and functional gradient at the interface results in stress concentration and a high rate of postoperative re-tears. Piezoelectric materials, known for modulating cellular functions and promoting stem cell proliferation and differentiation, have garnered increasing attention in tissue repair applications.MethodsIn this study, a biomimetic piezoelectric patch with progressive compositional and structural variations was designed and fabricated. The patch, composed of gelatin/PLGA/nHA/BTO, integrates aligned and random fiber structures. The aligned layer mimics the tendon-side structure of the rotator cuff tendon-bone interface, while the random layer replicates the bone-side structure.ResultsThe bioinspired patch exhibits excellent biocompatibility. The piezoelectric signals generated under ultrasound stimulation can induce osteogenic and tenogenic differentiation of stem cells, as well as regulate M2 polarization of macrophages, thereby promoting the repair and regeneration of supraspinatus tendon injury in a rabbit model of rotator cuff injury.DiscussionThis study highlights the potential of biomimetic piezoelectric patches in orthopedic rotator cuff repair and offers new possibilities for developing advanced materials to regenerate the rotator cuff tendon-bone interface.